Income and Feasibility of Hybrid Corn (Zea mays L.) Farming - Leovita, Angelia; Fauzi, Dian; Naufal, Deri (Universitas Djuanda, 2023)
Corn is a commodity that plays an important role as food for humans and livestock. When the poultry industry began to develop accompanied by an increase in rice production, the use of corn gradually shifted slightly to animal feed or fodder. This study aims to 1) describe the characteristics of corn petai 2) analyze the income of corn farmers 3) analyze the feasibility of corn farming in Luhak Nan Duo, West Pasaman Regency. Methods of taking Respondents in this study using Proportional Random Sampling with a total of 44 respondents. The data analysis method used is descriptive qualitative analysis and cost analysis (accounted costs and cash costs) analysis of income and receipts. The results showed that the characteristics of corn farmers in the Luhak Nan Duo area, West Pasaman Regency, gender were dominated by 75 percent male, respondents aged 39-45 years by 36.36 percent, junior high school education 40.90 percent, 3-5 years farming experience 34.09 percent, with a farmer's land area of 1-1.1 Ha by 59.09 percent, the status of owning land is 61.36 percent, the average income of corn farmers in Luhak Nan Duo District is Rp. 13,903,147.05 per farmer per land area per planting season with an R/C value of 1.89 so that farming in Luhak Nan Duo District is feasible to develop.